Multiparametric 18F-FDG and 68GA-DOTATOC PET Imaging in Bone Metastatic Meningioma Before Radionuclide Therapy: Assessment of Tumor Heterogeneity. (19th March 2022) - Mairal, Elise; Chevalier, Elodie; Imbert, Laetitia; Boursier-Joppin, Caroline; Verger, Antoine
Abstract: This report presents the case of a 61-year-old woman with assessment of fronto-temporo-sphenoidal refractory meningioma before radionuclide therapy with pretherapeutic 68 Ga-DOTATOC PET/CT. Given the discovery of osteolytic lesions, 18 F-FDG PET/CT is planned to search for the primitive origin. Meningioma bone metastasis is confirmed with spine biopsies. The presence of dedifferentiated meningioma lesions indicating that high somatostatin receptor expression does not necessarily coincide with areas of increased glucose metabolism. 18 F-FDG and 68 Ga-DOTATOC PET/CT allows optimal characterization of tumor heterogeneity and guide targeted therapeutic management before PPRT.